Primary cicatricial alopecias. (April 2010) - Alsantali, Adel; Shapiro, Jerry
Primary cicatricial alopecias are uncommon folliculocenteric inflammatory disorders that represent a ''trichologic emergency''. Unless correctly diagnosed and abruptly treated, these diseases can lead to permanent destruction of hair follicles and irreversible hair loss. Based on the predominant inflammatory cell type present, they are classified into lymphocytic, neutrophilic and mixed. The etiology and pathogenesis of many of these disorders are incompletely understood. A systematic review of classification, pathogenesis, clinical features, histopathologic findings and therapeutic options will be highlighted in this article.